CONCEPT OF THE PUBLIC GOODS REPRODUCTION IN ECONOMICS - M. Kichurchak (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2018)
The essence of the concept public goods reproduction has found out and the most important theory-gnoseological vectors of this process research have formed. The author has analyzed the system of theoretical views on the economic entity of reproduction. It was defined this economic category was multivariable. It was grounded the multiplicity of its subject essence became the prerequisite for distinguishing of the concept public goods reproduction . The main scientific approaches to understand the meaning of the public goods reproduction have considered. It was determined this economic category had synthetic character. Due to this the most adequate theoretical delineation of the concept public goods reproduction was represented and the basic reasons to determinate this theory-gnoseological principles were argued. The author had founded out that taking into account the existing criteria of the public goods classification their reproduction would scrutinized for the set of the theory-gnoseological vectors. Thereupon the scientific approaches to provide the integrity of the public goods reproduction vision and determine its many-sided nature were formed.